2018
DOI: 10.1016/j.amjcard.2018.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Use of Red Blood Cell Transfusion After Acute Coronary Syndrome to Long-Term Mortality

Abstract: Registry studies have associated red blood cell (RBC) transfusion with increased in-hospital mortality in patients with acute coronary syndrome (ACS). The impact on long-term mortality after 1-year follow-up remains unknown. Consecutive patients with ACS (n = 2,009) of a prospective Genetic Predisposition of Coronary Artery Disease cohort were followed for a median of 8.6 years (95% confidence interval [CI] 8.59 to 8.69). After discharge, 1,937 (96%) patients survived for over 30 days. Of those survivors, a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…This applies both to short-term and long-term mortality [3,[5][6][7][8]. A similar trend has been found not only after cardiac surgery but also after acute coronary syndrome [9,10]. In some studies, a higher impact on mortality has been observed in low-risk patients [6].…”
Section: Introductionsupporting
confidence: 60%
“…This applies both to short-term and long-term mortality [3,[5][6][7][8]. A similar trend has been found not only after cardiac surgery but also after acute coronary syndrome [9,10]. In some studies, a higher impact on mortality has been observed in low-risk patients [6].…”
Section: Introductionsupporting
confidence: 60%
“…The amount of transfusion in our matched cohort (median: 2; IQR: 2-4 units) was lower than that previously reported in patients with AMI (median: 8; IQR: 4-17.5 units). 23) Blood transfusions have been implicated in dose-dependent adverse effects. 24) Second, there are differences in the nature of the diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, a transfusion appeared to have beneficial or neutral effects on mortality at Hb levels below 8.0 g/dL, and harmful effects above 10 g/dL. [13,14] The symptoms of chronic anemia are tiredness, weakness, headache, vertigo, angina, exercise intolerance, and dyspnea. The underlying cause is most likely iron deficiency anemia or anemia based on other nutritional deficiencies.…”
Section: Discussionmentioning
confidence: 99%